Survey of psychosocial support provided by UK paediatric oncology centres. Issue 8 (26th April 2005) - Mitchell, W; Clarke, S; Sloper, P
Abstract : Aim: To obtain a comprehensive overview of current patterns of psychosocial support provided by National Health Service (NHS) paediatric oncology treatment centres across the UK. Methods: A postal questionnaire was sent to co-ordinators in the UK Children's Cancer Study Group (a professional body that is responsible for the organisation of treatment and management of childhood cancer in the UK) in 21 treatment centres and three separate Teenage Cancer Trus units. A range of psychosocial topics were explored, including ratio of staff providing support to patients; facilities provided for children and families; psychosocial support services such as support groups; information provision; and transition support. Results: There were many good areas of support provided by centres, but there was also a lack of standard practices and procedures. All centres employed social workers, play specialists, and paediatric oncology outreach nurses, but patient to staff ratios varied across centres. The poorest staff provision was among psychologists, where patient to staff ratios ranged from 132:1 to 1100:1. Written information was standard practice, while provision of other types of information (audiovisual, online) varied; none of the centres provided audio information specifically for children/young people. Conclusion: This variability in practices among centres frequently occurred, as centres rarely had procedures formally agreed or recorded in writing. British government policy currently seeks to develop standards and guidelines of care throughout the National Health Service. This study further demonstrates the importance of standards and the need to agree guidelines for the provision of psychosocial support for children/young people and their families throughout the course of the illness.